Assessing the Potential of Interfuel Substitution and Energy Efficiency as Environmental Policy Instruments in Selected Asian Countries - Alfonso, Cristina Lim (Curtin University, 2020)
Fuel switching and energy efficiency policies are studied to determine their potential to reduce carbon dioxide emissions. In addition, the thesis also investigates the economic impacts of changes in the energy mix due to these policies. The countries covered in this study are China, Japan, Korea, Indonesia, Malaysia, Singapore, Thailand and the Philippines. The results show that these energy policies mitigate carbon dioxide emissions without severely affecting the performance of the Asian economies.